Photodynamic properties of tungsten iodide clusters incorporated into silicone: A2[M6I8L6]@silicone. Issue 37 (10th June 2020) - Hummel, Thorsten; Dutczak, Danuta; Alekseev, Alexander Y.; Adamenko, Lyubov S.; Shestopalov, Michael A.; Mironov, Yuri V.; Enseling, David; Jüstel, Thomas; Meyer, Hans-Jürgen
Abstract : The light-induced antibacterial and antifungal properties of A2 [M6 I8 L6 ] with M = Mo and W, A = organic cation, L = ligand have been studied. Abstract : The light-induced antibacterial and antifungal properties of A2 [M6 I8 L6 ] with M = Mo and W, A = organic cation, L = ligand have been studied. The photoactive compounds (TBA)2 [W6 I8 (C7 H7 SO3 )6 ] and (TBA)2 [W6 I8 (COOCF3 )6 ] have been incorporated into a permeable silicone matrix and were measured for their application in the decomposition of multi-resistant bioactive species (hospital germs) such as S. aureus and P. aeruginosa as well as fungi. In addition, we present a new high volume synthesis route for these types of cluster compounds departing from the soluble compound W6 I22 .